Comparing the efficacy of four different protocols for eradicating of helicobacter pylori infection in Ahvaz, southwest Iran - Masjedizadeh, Abdolrahim; Zaeemzadeh, Narjes; Mard, Seyyed Ali; Vanani, Ghazal Salehi (Gastroenterology Review/Przegląd Gastroenterologiczny, 2015)
Introduction : Helicobacter pylori ( H. pylori ) is the common cause of many gastrointestinal diseases, especially peptic ulcer. Therefore, a successful treatment of this infection decreases the financial burden on health systems. Aim: Different combinations of antibiotics are used for the eradication of this bacterium worldwide. The goal of this study is to compare the efficacy of four different protocols used for this purpose in Ahvaz. Material and methods : A total number of 400 patients with H. pylori infection were randomly divided into four groups (100 in each): (1) OAC: omeprazole (20 mg/b.i.d.), amoxicillin (1000 mg/b.i.d.), clarithromycin (500 mg/b.i.d.) for 10 days. (2) OCF: omeprazole (20 mg/b.i.d.), ciprofloxacin (500 mg/b.i.d.), furazolidone (100 mg/b.i.d.) for 10 days. (3) OBAM: omeprazole (20 mg/b.i.d.), bismuth subcitrate (240 mg/b.i.d.), amoxicillin (1000 mg/b.i.d.), metronidazol (500 mg/b.i.d.) for 14 days. (4) OBTM: omeprazole (20 mg/b.i.d.), bismuth subcitrate (240 mg/b.i.d.), tetracycline (500 mg/b.i.d.), metronidazol (500 mg/b.i.d.) for 14 days. At the end the viability of the bacterium was assessed by C14 urea breath test. Results: The rate of H. pylori eradication was 92%, 59%, 73%, and 76% in OAC, OCF, OBAM, and OBTM groups, respectively (based on intention to treat analysis). The eradication rate was 93.9%, 62.1%, 77.7%, and 84.4% in OAC, OCF, OBAM, and OBTM groups, respectively (based on per protocol analysis). There was a statistically significant increase in eradication rate in the OAC group in comparison with the others (p < 0.001). Conclusions : Standard triple therapy (omeprazole, amoxicillin, clarithromycin) remains the most effective regimen for H. pylori eradication in Ahvaz.